Produktivitas dan Perbandingan Produksi Resin Pinus Merkusii Jungh Et De Vriese terhadap NPS yang Ditetapkan Perum Perhutani - Titik Wisnu Wardhana; Arip Wijayanto; Nurmadina; Darwitono (Fakultas Kehutanan Universitas Jambi, 2019)
The aims of this study were to investigate pine resin productivity in Sub Forest Management Unit (SFMU) Ponorogo Barat based on seasonal variation, to investigate the effect of number of trees against pine resin production annually, and to compare pine resin production against NPS determined by Perum Perhutani. This study used secondary data from SFMU Ponorogo Barat. Data was analysed with microsoft office excel. The result of this study showed that pine resin productivity in dry season (1.10 kg/tree to 1.85 kg/tree) was higher than that in wet season (0.81 kg/tree to 1.53 kg/tree). The annual resin production was affected by number of trees. The range of pine resin productivity is 1.91 kg/tree/year to 3.39 kg/tree/year. The comparison between NPS determine by Perum Perhutani and average of resin production percentage monthly and quarterly showed that slightly different, i.e. Â± 1% to 2%. and Â± 1% to 3% respectively. Keywoords: Pine resin, Productivity, Seasonal variation, NPS